2019
DOI: 10.32479/ijeep.8089
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oil Prices on the Global Competitiveness of National Economies

Abstract: The influence of various factors on the competitiveness of national economies is investigated in many articles, however, there is little research on the impact of resource prices on it. This article aims to examine the effect of crude oil prices on the global competitiveness of both producing countries and countries consuming oil. Based on annual data from 60 countries for 2006-2017, a regression analysis of panel data with fixed effects shows that exceeding the annual growth rate of oil prices over gross dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Based on annual data for the years 2006-2017, the researchers studied the impact of crude oil prices on global competitiveness in 60 oil-producing and oil-consuming countries by conducting fixed -effect panel data regression analysis and concluded that the annual growth rate of oil prices is higher than GDP growth. increasing the rate of growth more than doubles the growth rate of the Global Competitiveness index for oil-exporting countries compared to non-oil-exporting countries (Mukhamediyev and Temerbulatova, 2019). Mukhtarov et al (2019) investigated the effect of oil prices on economic growth, exports, inflation and exchange rate in Azerbaijan using Johansen cointegration and VECM methods based on the data covering the years 2005:01-2019:01 and came to the conclusion that the variables there is a long -term relationship between the impulse response and results decomposition tests show that oil prices have a positive and statistically significant effect on economic growth, exports and inflation, on the other hand, oil prices have a negative effect on the exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on annual data for the years 2006-2017, the researchers studied the impact of crude oil prices on global competitiveness in 60 oil-producing and oil-consuming countries by conducting fixed -effect panel data regression analysis and concluded that the annual growth rate of oil prices is higher than GDP growth. increasing the rate of growth more than doubles the growth rate of the Global Competitiveness index for oil-exporting countries compared to non-oil-exporting countries (Mukhamediyev and Temerbulatova, 2019). Mukhtarov et al (2019) investigated the effect of oil prices on economic growth, exports, inflation and exchange rate in Azerbaijan using Johansen cointegration and VECM methods based on the data covering the years 2005:01-2019:01 and came to the conclusion that the variables there is a long -term relationship between the impulse response and results decomposition tests show that oil prices have a positive and statistically significant effect on economic growth, exports and inflation, on the other hand, oil prices have a negative effect on the exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It will be imperative to lift the level of private finance and investment in the SDGs in all countries, especially low-and middleincome countries with rising populations. This includes both portfolio investment and direct investment, both domestic and foreign [13]. It also contains mobilizing private sector expertise and scaling capabilities, ranging from science, operational capacities, technological and research skills to the innovation, implementation of business.…”
Section: The Role Of Partnerships In Increasing the Level Investment mentioning
confidence: 99%
“…Consequently, non-oil competitiveness decreases and reduces the penetration rate of national products in the world economy. Mukhamediyev and Temerbulatova (2019) stated that when oil prices increase it allows countries to gain a financial surplus which can encourage economic decisionmakers to postpone economic reforms required to improve competitiveness. On the other hand, these surpluses can contribute to the reduction of the global competitiveness index, especially if these massive inflows of petro dollars will be spent on the acquisition of imported consumer goods.…”
Section: Introductionmentioning
confidence: 99%